Physics alternative to practical gce o level 1995-2011((yearly) worked solutions) - Ahmed, masood (Redspot pub; Pakistan, 2011)
"Physics Alternative to Practical GCE O-Level 1995-2011 (Yearly) Worked Solutions" provides detailed solutions to past practical exam questions, helping students understand experimental techniques and improve their performance in the Cambridge O-Level Physics Alternative to Practical exam.